Experimental Determination of GPR Groundwave Sampling Depth as a Function of Data Acquisition Parameters - Crist, Taylor; Nickel, Crystal (My University, 2010)
Ground penetrating radar (GPR) groundwaves can be used to measure the near-surface soil water content. Previous research has shown that the sampling depth of GPR groundwaves is frequently dependent when adjacent soil layers have highly contrasting soil water contents. This experiment investigated how the GPR groundwave sampling depth varies as a function of frequency and antenna offset in a natural soil during gradual infiltration and drying.
Color poster with text, images, and graphs.
Keywords: Hydrology--Measurement; Soil moisture--Measurement; Ground penetrating radar; Posters